Comparative analysis of macular characteristics in mCNV and contralateral eyes - Huang, Gongyu; She, Xiangjun; Zhang, Yun; Zhang, Zongduan; Shen, Lijun (Frontiers in Medicine, 2024)
Purpose To illustrate the characteristics of perforating scleral vessels in macular regions between mCNV eyes and contralateral eyes in unilateral mCNV patients. Methods This was a retrospective study that included patients with unilateral naive mCNV. The study aimed to identify and analyze the distribution of perforating scleral vessels (PSVs) in the macular region of mCNV eyes and contralateral eyes. The central macular choroidal thicknesses (mChT) were measured using optical coherence tomography angiography (OCTA). The grades of myopic atrophic maculopathy (MAM) and macular myopic diffuse chorioretinal atrophy (DCA) were evaluated within groups. The number of PSVs and mChT were compared between contralateral and mCNV eyes based on the grade of DCA. The ROC curves were utilized to explore the diagnostic indexes for mCNV. Results A total of 102 eyes from 51 patients with unilateral mCNV were included. There was no significance in the severity of MAM or the grade of DCA between mCNV eyes and contralateral eyes (p = 0.074, p = 0.054, respectively). The mean number of PSVs in mCNV eyes was fewer than the contralateral eyes [1.00 (1.00–2.00) vs. 2.00 (0.75–3.00), p = 0.030]. The mChT in mCNV eyes was thinner than the contralateral eyes [36.00 (25.00–53.75) μm vs. 46.00 (31.00–75.25) μm, p = 0.001]. The mean grade of DCA in mCNV eyes was higher than that in contralateral eyes [3.00 (3.00–3.00) vs. 3.00 (2.00–3.00), p = 0.004]. When DCA involved the macular region, there were more PSVs in contralateral eyes than in mCNV eyes [1.50 (1.00–2.00) vs. 2.00 (1.00–3.00), p = 0.042]. Similarly, when DCA involved the foveal region, there were more PSVs in contralateral eyes than in mCNV eyes [1.50 (1.00–2.00) vs. 3.00 (2.00–4.00), p = 0.004]. The grade of DCA and mChT were valuable factors for predicting mCNV eyes (AUC = 0.6566, p = 0.021; AUC = 0.6304, p = 0.029; respectively). When the extent of DCA exceeded the foveal region, the count of PSVs was a good diagnostic factor for predicting mCNV (AUC = 0.7430, p = 0.003). Conclusion The mean amount of PSVs was significantly lower in the mCNV eyes compared to the contralateral eyes. When the extent of DCA exceeded the foveal region, the count of PSVs was a good diagnostic factor for predicting mCNV. Myopic eyes with a higher grade of DCA and a thinner mChT were more likely to develop mCNV.